ПРИМЕНЕНИЕ “СКАФФОЛДИНГ”- ПОДХОДА В ОБУЧЕНИИ ИНОСТРАННЫМ ЯЗЫКАМ УЧАЩИХСЯ НАЧАЛЬНОЙ ШКОЛЫ - Ибраимова, Г. (SCIENCE and SOCIETY, 2025)
This article discusses the role of scaffolding strategies such as modeling, think-alouds, sentence starters and guided practices in teaching English to primary school students. These methods enable teachers to provide structured support that gradually shifts responsibility to students, promoting both language acquisition and critical thinking.
Keywords: scaffolding; english language teaching; primary school students; primary education; language acquisition; educational reform; modeling; guided practice